PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL)UNTUKMENINGKATKAN HASIL BELAJAR IPS KELAS V SD METHODIST TELUK PULAI KECAMATAN PASIR LIMAU KAPAS - Antosa, Zariul Antosa Zariul; Daud, Damanhuri Daud Damanhur; ', Erika (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :This research is motivated by low yields social studies students, with a grade average of 63.50. While the completeness criteria Minimum value (KKM) IPS is 65 Among students who were 23 people just 9 students who achieve KKM with classical completeness 39%. This research is Classroom Action Research (CAR) conducted aims to improve student learning outcomes IPS Gulf fifth grade elementary Methodist Teluk Pulai Kecamatan Pasir Limau Kapas by applying a learning model Contextual Teaching And Learning. Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the results obtained by studying the average learning outcome measures 63.50 before rising to 83.35 in Deuteronomy Daily Cycle II. Increased activity of the teachers at the meeting 60.71 1 82.14 on the first cycle to the second cycle of the meeting 2. Student activity increased from 50 at the first meeting of 1 cycle of 2 to 75 at the meeting of the second cycle. The results of research in the Gulf fifth grade elementary Methodist Teluk Pulai Kecamatan Pasir Limau Kapas that the application of learning models Contextual Teaching and Learning can improve student learning outcomes IPS Gulf fifth grade elementary Methodist Teluk Pulai Kecamatan Pasir Limau Kapas. Keywords: Model Contextual Teaching and Learning, IPS Learning Outcomes